Validity and reliability of a questionnaire on seatbelt attitude and practice towards road traffic regulations among residents in Kubang Kerian, Kelantan / Nur Syuhaidah Talib - Talib, Nur Syuhaidah (Bachelor of Science (Hons) Statistics, 2015)
This project focuses on the validity and reliability of a questionnaire for evaluating seatbelt attitude and seatbelt practice towards road traffic regulations among residents in Kubang Kerian, Kelantan. The road traffic regulation is defined as a system of organizational and technical measures designed to increase the speed and safety of traffic. The essence of road traffic regulation is to make certain actions obligatory, forbidden, or recommended for drivers of vehicles and for pedestrians in the interests of ensuring speed and safety. Lack of driver‟s attitudes and practices against the road traffic regulation would cause road traffic accidents. Accidents occur when a vehicle on the road that collides with an object or another vehicle. The purpose of this paper is to determine the validity and reliability of the questionnaire on seatbelt attitude and practice towards road traffic regulations among residents in Kubang Kerian, Kelantan. This study involved 150 of respondents by using cross-sectional study. This study was done by distributing questionnaires to all residents in Kubang Kerian, Kelantan. The result shows that only one item remaining for each seatbelt attitude and seatbelt practice in Exploratory Factor Analysis (EFA). In conclusion, only one item was valid for seatbelt attitude and seatbelt practice, but there is less reliable for both seatbelt attitude and seatbelt practice. Thus, improvement should be performed in order to increase the validity and reliability of a questionnaire